The Effect of Kinematic Conditions and Synovial Fluid Composition on the Frictional Behaviour of Materials for Artificial Joints - Nečas, David; Vrbka, Martin; Křupka, Ivan; Hartl, Martin (Materials (Basel, Switzerland), 2018)
The paper introduces an experimental investigation of frictional behaviour of materials used for joint replacements. The measurements were performed using a ball-on-disc tribometer, while four material combinations were tested; metal-on-metal, ceramic-on-ceramic, metal-on-polyethylene, and ceramic-on-polyethylene, respectively. The contact was lubricated by pure saline and various protein solutions. The experiments were realized at two mean speeds equal to 5.7 mm/s and 22 mm/s and two slide-to-roll ratios, −150% and 150%. It was found that the implant material is the fundamental parameter affecting friction. In general, the metal pair exhibited approximately two times higher friction compared to the ceramic. In particular, the friction in the case of the metal varied between 0.3 and 0.6 while the ceramic pair exhibited friction within the range from 0.15 to 0.3 at the end of the test. The lowest friction was observed for polyethylene while it decreased to 0.05 under some conditions. It can be also concluded that adding proteins to the lubricant has a positive impact on friction in the case of hard-on-hard pairs. For hard-on-soft pairs, no substantial influence of proteins was observed. The effect of kinematic conditions was found to be negligible in most cases.
Keywords: material; kinematic conditions; friction; proteins; joint replacement